Outcome of Patients: Early Nephrologist Consultation in Cardiorenal Syndrome - Jenkriangkrai, Suchart; Parapiboon, Watanyu; Simtharakaew, Tanin; Niyomsirivanich, Piti (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2025)
The Cardiac Intensive Care Unit (CCU) at Maharat Nakhon Ratchasima Hospital has implemented a rapid nephrology consultation process for patients with acute kidney injury (AKI) secondary to heart failure. However, it remains unclear whether these measures have significantly impacted patient outcomes. The aims of this study were to investigate mortality rates, clinical characteristics, and factors associated with 28-day mortality among acute kidney injury (AKI) patients. This retrospective descriptive and analytical study used Cox regression analysis to evaluate the survival rate. Data were collected from the medical records of patients diagnosed with AKI in the CCU between November 2020 and August 2021. A total of 52 patients were included, with a mean age of 67.9+ 11.2 years. The majority were male patients (71.2%). At the time of nephrologist consultation, most patients (78.8%) were in stage 2 of kidney injury. The predominant cardiac diagnosis was ST-elevation myocardial infarction (STEMI)in 67.3% of cases. Treatment interventions included vasopressor medications (82.7%) coronary angiography (78.9%), and required an intra-aortic balloon pump (51.9%). The median cumulative fluid balance on day 5 was -1,119.0 mL (interquartile range: -2,859.5 to 1,616.0 mL). During hospitalization, the total follow-up period was 715 patient-days. with 27 deaths recorded, This Corresponds to an in-hospital mortality incidence of 9.4 per 100 patient-days (95%CI: 6.4-13.7). The median patient survival post-hospitalization was 19 days. Survival rates at 7, 14 and 28 days were 69.1% (95% CI: 0.546-0.426), 57.7% (95%CI: 0.426-0.702), and 39.4% (95%CI: 0.22-0.564), respectively. Significant factors associated with 28-day mortality included age ≥ 80 years (Adjusted Hazard Ratio: 4.66; 95%CI: 1.66-13.06; P=0.003) and sepsis (Adjusted Hazard Ratio 2.39;95%CI: 1.06-5.36; P=0.035). Therefore, AKI patients admitted to the CCU experience a high in-hospital mortality rate. Older age and sepsis are critical factors associated with 28-day mortality. These findings underscore the urgent need for targeted interventions to improve outcome in this high-risk patient population.